2020
DOI: 10.1002/path.5566
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide mutation analysis in precancerous lesions of endometrial carcinoma

Abstract: Clinicopathological evidence supports endometrial atypical hyperplasia (AH) or endometrial intraepithelial neoplasia as the precursor of uterine endometrioid carcinoma (EC), the most common gynecologic malignancy. However, the pathogenic progression from AH to EC remains unclear. Here, we employed whole-exome sequencing to identify somatic mutations and copy number changes in micro-dissected lesions from 30 pairs of newly diagnosed AH and EC. We found that all but one pair of AHs shared the same DNA mismatch r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…EAH/EIN is the precursor lesion of almost all endometrioid carcinomas and a subset of serous carcinomas [58]. The mutational profile of EAH/EIN and the concurrent EC is highly concordant [18,59–62] in the majority of cases; however, Li et al showed that, in 5 out of 30 EAH/EIC cases with concurrent EEC, the EAH/EIC and EC shared less than 5% of the mutations identified, indicating clonality but with a high degree of divergence [62]. Serous intraepithelial carcinoma (SEIC) is characterized by pre‐existing endometrial glands lined by markedly atypical glandular epithelial cells in the absence of invasive disease.…”
Section: Precursors Of Endometrial Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…EAH/EIN is the precursor lesion of almost all endometrioid carcinomas and a subset of serous carcinomas [58]. The mutational profile of EAH/EIN and the concurrent EC is highly concordant [18,59–62] in the majority of cases; however, Li et al showed that, in 5 out of 30 EAH/EIC cases with concurrent EEC, the EAH/EIC and EC shared less than 5% of the mutations identified, indicating clonality but with a high degree of divergence [62]. Serous intraepithelial carcinoma (SEIC) is characterized by pre‐existing endometrial glands lined by markedly atypical glandular epithelial cells in the absence of invasive disease.…”
Section: Precursors Of Endometrial Carcinomamentioning
confidence: 99%
“…In recent work comparing resolving and progressing EAH/EIN and comparing EAH/EIN and subsequent carcinoma, Russo et al identified NSMP, MMRd, and p53abn EAH/EIN lesions [61,71]. Evidence of clonal evolution has been demonstrated in whole‐exome sequencing studies of paired EAH/EIN and concurrent EC (mostly of NSMP and MMRd molecular subtypes [62]. p53abn : This is the prototypical type II EC and accounts for a large majority of serous ECs.…”
Section: Morphological Features Of the Endometrial Carcinoma Precursomentioning
confidence: 99%
See 1 more Smart Citation
“…4a). ARID1A and PTEN are two key tumor suppressors in endometrioid carcinoma, the most common type of human uterine carcinoma and ARID1A mutation and loss of its expression correlate with tumor invasion in human endometrial carcinoma [44][45][46][47][48] . Deletion of Arid1a significantly accelerates tumor progression of Pten-deleted endometrial and ovarian carcinomas as evidenced by marked invasion and metastasis in genetically engineered mouse models 49,50 .…”
Section: Validation Of New Organoids In Vivomentioning
confidence: 99%
“…In the uterine cervix or vulva, precancers driven by HPV often resolve spontaneously [17,18], a phenomenon undocumented in the endometrium. These factors could make the endometrium a useful model system for the systematic study of the formation and progression of early precancers [19].…”
Section: Introductionmentioning
confidence: 99%